Regulated expression of foreign genes in vaccinia virus under the control of bacteriophage T7 RNA polymerase and the Escherichia coli lac repressor. - Alexander, W A (1992)
The gene encoding bacteriophage T7 RNA polymerase (T7gene1) was placed under the control of regulatory elements from the Escherichia coli lac operon to construct an inducible vaccinia virus expression system consisting entirely of prokaryotic transcriptional machinery. Regulated expression of T7 RNA polymerase was necessary to construct a stable recombinant vaccinia virus harboring a T7 promoter; otherwise, uncontrolled expression led to interference with endogenous virus replication. To this end, the gene encoding the repressor protein of the lac operon was fused to a viral early/late promoter so that it was expressed constitutively, and the lac operator was interposed between a viral major late promoter and T7gene1. Greater than 99% repression of T7 RNA polymerase, which was relieved approximately 80-fold in the presence of the inducer isopropyl-beta-D-thiogalactopyranoside (IPTG), was obtained. An expression cassette containing a T7 promoter-controlled beta-galactosidase reporter gene was recombined into a different region of the viral genome containing T7gene1. A stable, double recombinant virus was isolated and grown to a high titer. In the absence of inducer, beta-galactosidase expression was substantially repressed. Addition of increasing amounts of IPTG induced expression of beta-galactosidase to the point of suppression of viral replication. This hybrid vaccinia virus system (Vac/Op/T7) has potential applications for the efficient bioproduction of a wide variety of gene products.